The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1136/heartjnl-2015-308796
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of contemporary stress echocardiography in morbid obesity for the assessment of coronary artery disease

Abstract: Contemporary SE has excellent feasibility and positive predictive value and resulted in appropriate risk stratification of symptomatic patients with significant obesity. A normal SE portends an excellent outcome over the short-intermediate term in this high-risk patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…The study by Shah et al 2 definitely confirms that the addition of contrast for left ventricle opacification makes stress echocardiography feasible in this subset of patients too, either using pharmacological or exercise stress, which is possibly even more impressive, since exercise is the most demanding stressor to acquire good-quality images. In this specific regard, I would add a word of caution on the use of exercise echo in such morbidly obese subjects, since having such patients both exercise sufficiently and at the same time acquiring high-quality images is achievable only by very skilled operators, even with the aid of ultrasound contrast media.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The study by Shah et al 2 definitely confirms that the addition of contrast for left ventricle opacification makes stress echocardiography feasible in this subset of patients too, either using pharmacological or exercise stress, which is possibly even more impressive, since exercise is the most demanding stressor to acquire good-quality images. In this specific regard, I would add a word of caution on the use of exercise echo in such morbidly obese subjects, since having such patients both exercise sufficiently and at the same time acquiring high-quality images is achievable only by very skilled operators, even with the aid of ultrasound contrast media.…”
mentioning
confidence: 78%
“…This extreme obesity category was also the specific target population of the interesting study by Shah et al 2 in their Heart publication.…”
mentioning
confidence: 99%
“…All SE studies were performed using either treadmill exercise or pharmacological (dobutamine-atropine) stress as we have previously described 10. In summary, exercise stress was the preferred modality, and in patients unsuitable for exercise, dobutamine was infused in 3 min dose increments, starting from 10 µg/kg/min and increasing to 20, 30 and 40 µg/kg/min if there were no resting wall motion abnormalities, otherwise a viability protocol was used commencing at 5 µg/kg/min.…”
Section: Methodsmentioning
confidence: 99%
“…Contrast stress echocardiography with additional myocardial perfusion assessment (cSE‐WMP) has demonstrated further increase in predictive accuracy for hard cardiac events in patients with suspected or known CAD, either during dobutamine10, 11 or vasodilator12, 13, 14 stress. As far as WM assessment is concerned, cSE‐WMP also has the advantage of maximizing test feasibility over standard stress echocardiography, with quality of acoustic windows not representing an issue when taking advantage of ultrasound contrast media 15. Still, the few studies assessing cSE‐WMP for prognosis do not address its value specifically in predicting true ischemic events (cardiac death and nonfatal acute myocardial infarction [MI]),10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and it is not known how the use of cSE‐WMP as a gatekeeper to coronary angiography and subsequent revascularization does relate to long‐term outcome in subsequently revascularized and nonrevascularized patients.…”
Section: Introductionmentioning
confidence: 99%
“…As far as WM assessment is concerned, cSE‐WMP also has the advantage of maximizing test feasibility over standard stress echocardiography, with quality of acoustic windows not representing an issue when taking advantage of ultrasound contrast media 15. Still, the few studies assessing cSE‐WMP for prognosis do not address its value specifically in predicting true ischemic events (cardiac death and nonfatal acute myocardial infarction [MI]),10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and it is not known how the use of cSE‐WMP as a gatekeeper to coronary angiography and subsequent revascularization does relate to long‐term outcome in subsequently revascularized and nonrevascularized patients. Previous cSE‐WMP studies reported only on combined end points with prevalence of all‐cause deaths, half of them represented by cancer deaths, pneumonia, or other diseases that may not be directly influenced by coronary ischemia at stress testing 10, 11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%